2014
DOI: 10.1504/ijpti.2014.064165
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of low cost evaporative cooling systems to minimise postharvest losses of tomatoes (Roma vf) around Woreta, Ethiopia

Abstract: Low cost evaporative cooling systems were developed and investigated for their cooling efficiency to improve the shelf life of tomatoes. Average cooling efficiencies of bamboo jute and pot in pot coolers before being loaded with tomatoes were 82% and 79% and after being loaded were 67.6% and 61.6%, respectively. Physiological weight losses were 1.03%, 1.32% and 1.42% for bamboo jute, pot in pot coolers and ambient storage, respectively. The sensory results revealed that the shelf life of tomatoes were 5, 19 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
(12 reference statements)
0
2
1
Order By: Relevance
“…The sharp decrement in cooling efficiency observed from 4:00 p.m. to 10:00 p.m. may be due to the decrease in dry bulb temperature and the intensity of solar radiation. In the current study, the average cooling efficiency was 75.83%, which was greater than that reported in some earlier studies 17,28 but lower than that reported in others. 5,29,30 The differences in cooling efficiency in these studies may have occurred because different EC systems were developed and used by various researchers and studied in different climates.…”
Section: Cooling Efficiencycontrasting
confidence: 78%
“…The sharp decrement in cooling efficiency observed from 4:00 p.m. to 10:00 p.m. may be due to the decrease in dry bulb temperature and the intensity of solar radiation. In the current study, the average cooling efficiency was 75.83%, which was greater than that reported in some earlier studies 17,28 but lower than that reported in others. 5,29,30 The differences in cooling efficiency in these studies may have occurred because different EC systems were developed and used by various researchers and studied in different climates.…”
Section: Cooling Efficiencycontrasting
confidence: 78%
“…It is estimated that about 20 to 50% of harvested tomato is lost during harvesting, transportation, storage and before they reach consumers (Pila et al, 2010). The magnitude of tomato post-harvest losses in many African countries, like Ethiopia, is eventually very high and hard to estimate (Emana et al, 2017;Woldemichael & Demelash, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These undesirable effects of excessive temperature are directly linked to higher respiration rates, transpiration and ethylene production. Odesola and Onyebuchi [5] noted that lower storage temperatures and higher relative humidity will generally maintain the nutritional quality, appearance and flavour with minimal effect on softening and wilting of fresh produce. Mechanical refrigeration is one of the techniques used to achieve high relative humidity and low storage temperatures in developed countries [6].…”
Section: Introductionmentioning
confidence: 99%